2016
DOI: 10.1111/apa.13378
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol was effective in treating cutaneous infantile haemangiomas in Thai children

Abstract: Propranolol was effective in treating infantile haemangiomas, and combining it with prednisolone achieved no significant differences in treatment outcome. Cases should be monitored for hypoglycaemia and hypotension. More data on using propranolol for infantile haemangiomas are needed, including long-term follow-up studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…This cutaneous lesion has its own characteristics of natural history of growth pattern, which consists of 3 phases: proliferative, involuting, and involuted. 21,22 Cutaneous lesions usually occur as preliminary light patches before growing rapidly in the proliferative phase. This pattern can be seen within a few weeks to a few months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cutaneous lesion has its own characteristics of natural history of growth pattern, which consists of 3 phases: proliferative, involuting, and involuted. 21,22 Cutaneous lesions usually occur as preliminary light patches before growing rapidly in the proliferative phase. This pattern can be seen within a few weeks to a few months.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some problematic hemangiomas that require early treatment. 23 The current treatment of choice is oral or topical propranolol, which many studies 21,[24][25][26] from around the world have shown to be effective in treating cutaneous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This may due to the fact that the early cutaneous lesion of infantile hemangioma usually presents as a faint erythematous patch that is difficult to be seen within the first 5 days of life. 14,15 More over infantile hemangiomas are more common in preterm infants, while the population in the present study were all full-term born which may affect the distribution of the cutaneous findings.…”
Section: Discussionmentioning
confidence: 78%
“…While not statistically significant, interestingly, 62.5% of the children in this study who experienced complications were initiated at a 2 mg/kg/day dose, compared with 27.8% of the general study population. A small Thai cases series found children who were given 2 mg/kg/day of propranolol who experienced hypoglycaemia 16 did not experience hypoglycaemia when dropped to 1 mg/kg/day and then slowly increased in 0.5 mg/kg/day increments to 2 mg/kg/day. Herman et al 19 noted similarly in their study.…”
Section: Discussionmentioning
confidence: 99%